2018
DOI: 10.1016/j.juro.2018.05.080
|View full text |Cite
|
Sign up to set email alerts
|

Use of Automated Performance Metrics to Measure Surgeon Performance during Robotic Vesicourethral Anastomosis and Methodical Development of a Training Tutorial

Abstract: Automated performance metrics can distinguish surgeon expertise during vesicourethral anastomosis. The expert vesicourethral anastomosis technique was associated with more efficient movement and less tissue trauma. Standardizing robotic vesicourethral anastomosis and using a methodically developed tutorial may help improve robotic surgical training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 22 publications
0
48
0
Order By: Relevance
“…These instrument motion‐tracking and events metrics are derived from computer‐based data recording devices. Preliminary studies have shown that APMs can differentiate expert and novice surgeon performance in both laboratory and clinical settings . Our group has shown that APMs differentiate surgeon experience during the steps of RARP .…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…These instrument motion‐tracking and events metrics are derived from computer‐based data recording devices. Preliminary studies have shown that APMs can differentiate expert and novice surgeon performance in both laboratory and clinical settings . Our group has shown that APMs differentiate surgeon experience during the steps of RARP .…”
Section: Introductionmentioning
confidence: 81%
“…Baseline differences between patients in Group 1/ Experience and Group 2/Experience included preoperative IPSS (5 vs 4; P = 0.004) and prostate volume (50 vs 44 mL; P = 0.011 [ Table 7]). Group 1/Experience included a higher proportion of nerve-sparing procedures (83.4 vs 66.7%; P = [1][2][3][4][5][6][7][8][9] days; P = 0.049), and lower rate of low-grade (Clavien grade I-II) postoperative complications (6.7 vs 15.9%; P = 0.038). There was no significant difference in continence, erectile function or biochemical recurrence at 3, 6, 12, 18 or 24 months postoperatively (P > 0.05).…”
Section: Historical Cases Comparison Between Group 1/ Experience and mentioning
confidence: 99%
See 1 more Smart Citation
“…We also found that less robotic instrument articulation was used whilst operating in a deeper pelvis. In our prior study, more instrument articulation was an indicator of greater robotic surgical expertise . Specifically, expert surgeons (with >100 prior robotic surgical cases) had more instrument joint articulation during the VUA step than surgeons with less experience.…”
Section: Discussionmentioning
confidence: 88%
“…We assessed the influence of body habitus, bony pelvic measurements, prostate measurements, and surgeon experience (robotic surgical expert [with >100 prior robotic surgical cases] vs novice [with <100 prior robotic surgical cases]) on surgical performance, i.e., APMs, using multivariable linear regression analysis. Our prior work has confirmed that differences in surgical skills are apparent after 100 cases . As dropping bladder, vesicourethral anastomosis (VUA) and bilateral pelvic lymph node dissection (PLND) do not involve the prostate, no prostate measurements were included in analysis during these steps.…”
Section: Patients Subjects and Methodsmentioning
confidence: 99%